Analysis of Risk Factors Associated with Type 2 Diabetes Mellitus among Regional Government Organizations Employees - Andriana Ratna Ningrum; Irfansyah Baharuddin Pakki; Ike Anggraeni (Indonesian Journal of Global Health Research, 2026)
Type 2 diabetes mellitus was a major non communicable disease with an increasing prevalence among the productive-age population. Multiple risk factors, including sociodemographic characteristics, lifestyle behaviors, clinical conditions, and family history, were known to contribute to its development. Employees of Regional Government Organizations (RGO) represented a productive age group with a potentially high risk of type 2 diabetes mellitus. This study aimed to analyze risk factors associated with type 2 diabetes mellitus. A quantitative cross sectional study was conducted from January to February 2023 involving 3,313 RGO employees. A total of 1,955 respondents were selected using accidental sampling based on the Lemeshow formula. Data were collected through questionnaire, physical examinations, and random blood glucose measurements. The questionnaire was not subjected to validity and reliability testing, as the data were derived from direct measurements and interview findings. Statistical analyses were performed using chi-square tests and multiple logistic regression. The results showed that body mass index, sex, family history of diabetes mellitus, blood pressure, and history of heart disease were significantly associated with type 2 diabetes mellitus (p<0.05). In contrast, smoking behavior, physical activity, fruit and vegetable consumption, and history of stroke were not significantly associated. Multivariate analysis indicated that family history of diabetes mellitus was the most dominant risk factor (OR = 4.882). It was concluded that family history of diabetes mellitus was the strongest determinant of type 2 diabetes mellitus among RGO employees, emphasizing the importance of early screening and risk factor management in the productive age population.